In Vivo Fluorescence Imaging of Passive Inflammation Site Accumulation of Liposomes via Intravenous Administration Focused on Their Surface Charge and PEG Modification - Hisako Ibaraki; Akihiro Takeda; Naoki Arima; Naruhiro Hatakeyama; Yuuki Takashima; Yasuo Seta; Takanori Kanazawa (MDPI AG, 2021)
Nanocarriers such as liposomes have been attracting attention as novel therapeutic methods for inflammatory autoimmune diseases such as rheumatoid arthritis and ulcerative colitis. The physicochemical properties of intravenously administered nanomedicines enable them to target inflamed tissues passively. However, few studies have attempted to determine the influences of nanoparticle surface characteristics on inflammation site accumulation. Here, we aimed to study the effects of polyethylene glycol (PEG) modification and surface charge on liposome ability to accumulate in inflammatory sites and be uptake by macrophages. Four different liposome samples with different PEG modification and surface charge were prepared. Liposome accumulation in the inflammation sites of arthritis and ulcerative colitis model mice was evaluated by using in vivo imaging. There was greater PEG-modified than unmodified liposome accumulation at all inflammation sites. There was greater anionic than cationic liposome accumulation at all inflammation sites. The order in which inflammation site accumulation was confirmed was PEG-anionic > PEG-cationic > anionic > cationic. PEG-anionic liposomes had ~2.5× higher fluorescence intensity than PEG-cationic liposomes, and the PEG-liposomes had ~2× higher fluorescence intensity than non-PEG liposomes. All liposomes have not accumulated at the inflammation sites in healthy mice. Furthermore, cationic liposomes were taken up to ~10× greater extent by RAW264.7 murine macrophages. Thus, PEG-cationic liposomes that have the ability to accumulate in inflammatory sites via intravenous administration and to be taken up by macrophages could be useful.